Whole-Exome Sequencing Analysis of Oral Squamous Cell Carcinoma Delineated by Tobacco Usage Habits - Patel, Krishna; Bhat, Firdous Ahmad; Patil, Shankargouda; Routray, Samapika; Mohanty, Neeta; Nair, Bipin; Sidransky, David; Ganesh, Mandakulutur S.; Ray, Jay Gopal; Gowda, Harsha; Chatterjee, Aditi (Frontiers in Oncology, 2021)
Oral squamous cell carcinoma (OSCC) is a common cancer of oral cavity in India. Cigarette smoking and chewing tobacco are known risk factors associated with OSCC. However, genomic alterations in OSCC with varied tobacco consumption history is not well-characterized. In this study, we carried out whole-exome sequencing to characterize the mutational landscape of OSCC tumors from subjects with different tobacco consumption habits. We identified several frequently mutated genes, including TP53, NOTCH1, CASP8, RYR2, LRP2, CDKN2A, and ATM. TP53 and HRAS exhibited mutually exclusive mutation patterns. We identified recurrent amplifications in 1q31, 7q35, 14q11, 22q11, and 22q13 regions and observed amplification of EGFR in 25% of samples with tobacco consumption history. We observed genomic alterations in several genes associated with PTK6 signalling. We observed alterations in clinically actionable targets including ERBB4, HRAS, EGFR, NOTCH1, NOTCH4 and NOTCH3. We observed enrichment of signature 29 in 40% of OSCC samples from tobacco chewers. Signature 15 associated with defective DNA mismatch repair was enriched in 80% of OSCC samples. NOTCH1 was mutated in 36% of samples and harboured truncating as well as missense variants. We observed copy number alterations in 67% of OSCC samples. Several genes associated with non-receptor tyrosine kinase signalling were affected in OSCC. These molecules can serve as potential candidates for therapeutic targeting in OSCC.